Investments in farm land in Northern Ethiopia: a household-level analysis of the roles of poverty, tenure security, and conservation - Metkel Aregay Gebreeyosus; Haftu Etsay Kelebe; Teklay Negash Gebregziabher (Journal of Degraded and Mining Lands Management, 2020)
There is a long-standing debate on the relationship between land-related investments and tenure security and most studies in this sense fail to reach a concrete conclusion because of their focus on one side. This paper has employed a separate analysis for short-run farm investments as represented by spending on farm inputs and long-term investments as represented by hours spent on stone bund building in an attempt to solve this problem. Two Tobit models were estimated to analyze household level determinants of land-related investment decisions by smallholder farmers in Ethiopia and its tenure security implications. The findings revealed that there is no meaningful and significant relationship between tenure security and land-related investments decisions. Poverty status, rather, was found to exert significant negative pressure on investment decisions. Productivity, livestock holding, communal conservation around plot and participation in local government activities are found to be the major determinants of land investments.